2015
DOI: 10.1124/mol.114.094722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gαq on the Dynamics of M3-Acetylcholine Receptor–G-Protein–Coupled Receptor Kinase 2 Interaction

Abstract: G-protein-coupled receptor kinase 2 (GRK2) is a serine/ threonine kinase with an important function in the desensitization of G-protein-coupled receptors. Based on its ability to bind G-protein bg subunits as well as activated Ga q subunits, it can be considered as an effector for G-proteins. The recruitment of GRK2 to activated receptors is well known to be mediated by Gbg together with negatively charged membrane phospholipids. In the current study, we address the role of Ga q on the interaction of GRK2 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Interestingly, following receptor-mediated G protein-activation G␤␥ bound first with a delay of less than a second to GRK2, whereas G␣q joined the complex with a delay of about 3-4 s. The dissociation kinetics after agonist withdrawal was comparable to those of G protein reassembly-kinetics. We could not observe any major acceleration of G protein deactivation by GRK2 and therefore conclude that the RGS domain of GRK2 does not serve as a GTPase-activating protein (GAP) for G␣q (Wolters et al, 2015) in intact cells. In accordance with previous studies on the role of G␤␥, we found that the recruitment of GRK2 to the receptor via G␣q was not sufficient to allow for GRK2-mediated arrestin recruitment.…”
Section: Interaction Of Gq Protein Subunits With G Protein-coupled Rementioning
confidence: 71%
See 3 more Smart Citations
“…Interestingly, following receptor-mediated G protein-activation G␤␥ bound first with a delay of less than a second to GRK2, whereas G␣q joined the complex with a delay of about 3-4 s. The dissociation kinetics after agonist withdrawal was comparable to those of G protein reassembly-kinetics. We could not observe any major acceleration of G protein deactivation by GRK2 and therefore conclude that the RGS domain of GRK2 does not serve as a GTPase-activating protein (GAP) for G␣q (Wolters et al, 2015) in intact cells. In accordance with previous studies on the role of G␤␥, we found that the recruitment of GRK2 to the receptor via G␣q was not sufficient to allow for GRK2-mediated arrestin recruitment.…”
Section: Interaction Of Gq Protein Subunits With G Protein-coupled Rementioning
confidence: 71%
“…However, not all RGS domains induce an enhancement of the GTPase activity of G␣ subunits, but rather may serve as a G␣-binding element (Shankaranarayanan et al, 2008). FRET assays used by Wolters et al (2015) offer the possibility to study the kinetics of individual steps of the receptor-mediated G protein cascade in a very similar experimental setting and therefore help to analyze effects of regulatory proteins on G protein dynamics in intact cells. We found that activation of M 3 AChR led to a robust interaction of GRK2 with G␣q, as well as with G␤␥.…”
Section: Interaction Of Gq Protein Subunits With G Protein-coupled Rementioning
confidence: 98%
See 2 more Smart Citations
“…In experiments in which FRET amplitudes are shown, relative expression levels of fluorescently labeled proteins were determined as described before (Wolters et al, 2015). In brief, both fluorophores were excited individually and background fluorescence was subtracted for each channel.…”
Section: Methodsmentioning
confidence: 99%